Validity and reliability of MyLift app in determining 1-RM for deadlift and back squat exercises - Cetin, O.; Isik, O. (European Journal of Human Movement, 2021)
Smartphone technologies are seen as a rapidly developing field of research in physical activity research. However, it is important to use smartphone applications that have proven validity and reliability in performance measurement. This study aimed to determine the validity and reliability of the MyLift mobile app used for the determining estimated 1-RM for conventional deadlift and barbell back squat exercises. 10 junior male weightlifters ( Xage: 17.50 ± 1.27 years) voluntarily participated in the study. For the conventional deadlift and barbell back squat movements of the weightlifters, MyLift app measurements were obtained during the 1-RM test simultaneously with sub-maximal loads (75-85% 1-RM). Results obtained from MyLift app and actual 1-RM were compared with Bland-Altman plots. There was no significant difference between the estimated results obtained from MyLift app and the results obtained from the actual 1-RM test (p> 0.05), and the explanatory coefficient (Conventional deadlift: R2 = 0.99; Barbell back squat: R2 = 0.99) was found to be quite high. MyLift app used to determine estimated 1-RM is a very valid and reliable tool compared to the actual 1-RM test. The MyLift app can be used by athletes and coaches as a practical and valid measurement tool for determining 1-RM using sub-maximal loads.